2015
DOI: 10.1097/md.0000000000002064
|View full text |Cite
|
Sign up to set email alerts
|

Validation of T Stage According to Depth of Invasion and N Stage Subclassification Based on Number of Metastatic Lymph Nodes for Distal Extrahepatic Bile Duct (EBD) Carcinoma

Abstract: According to the current AJCC staging system, the T stage of distal extrahepatic bile duct carcinoma (EBD) is classified according to the extent of the tumor within or beyond the bile duct wall. However many invasive carcinoma accompany stromal desmoplasia that obscure lower boundary of bile duct wall; it is frequently difficult to clearly define the extent of tumors using the current T classification system. In this study, we validated an alternative T classification system by depth of invasion (DoI; T1: < 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 18 publications
6
47
3
Order By: Relevance
“…This heterogeneity required the predefinition of measurement methods according to the gross tumour morphology, an approach that is frequently applied for tumours such as cutaneous melanoma and early‐stage colorectal cancer. To date, two measurement methods have been reported for depth assessment in cholangiocarcinoma: DOI and ITT. It was reported previously that the measurability of DOI depended on tumour morphology, size and direction of sectioning of the resected specimen, but the measurability of ITT did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This heterogeneity required the predefinition of measurement methods according to the gross tumour morphology, an approach that is frequently applied for tumours such as cutaneous melanoma and early‐stage colorectal cancer. To date, two measurement methods have been reported for depth assessment in cholangiocarcinoma: DOI and ITT. It was reported previously that the measurability of DOI depended on tumour morphology, size and direction of sectioning of the resected specimen, but the measurability of ITT did not.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive tumour thickness (ITT) was defined as the vertical distance from the top of the tumour to the deepest invasive cells ( Fig . ), as reported previously. Microscopic perineural, lymphatic and venous invasion were not considered for this measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, retrieving enough regional LNs and accurately determining the cancer stage is important to determine the prognosis. The 5th AJCC staging system recommended to examine at least three LNs, but no evidence of the [26,27]. However, these reports did not mention the rate of LN positivity, according to the number of retrieved LNs, and the number of enrolled patients was too small.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies reporting the superiority of the 8th AJCC T stage over the 7th are limited. Two external validation studies failed to show significant survival discrimination among the proposed 8th T stage criteria [27,29], and one of these studies proposed different cutoff values for tumor invasion depth, based on T stage [29]. A previous study revealed that the new 8th AJCC T stage did not have better prognostic predictability than the 7th [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the bile duct, unlike the gastrointestinal tract, has a thin wall with a frequently obscured outermost boundary, potentially leading to an uncertain T assignment. In addition, the layer‐based T classification fails to stratify postoperative survival in patients with DCC. Thus, the conventional layer‐based T system has limited value in DCC.…”
Section: Introductionmentioning
confidence: 99%